2011
DOI: 10.1167/iovs.10-6543
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Italian Patients with Leber Congenital Amaurosis due to AIPL1 Mutations Highlights the Potential Applicability of Gene Therapy

Abstract: Using advanced imaging diagnostics we showed that maculopathy is a main feature of LCA4. We identified retinal areas at the posterior pole with surviving photoreceptors present even in adult LCA4 patients, which could be the target of gene therapy. The possible use of gene therapy for LCA4 is additionally supported by the protection from photoreceptor degeneration observed in Aipl 1-/- mice and by the high levels of photoreceptor transduction in the absence of toxicity observed after AAV2/8 delivery to the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 38 publications
7
33
0
Order By: Relevance
“…For both AIPL1 and GUCY2D, proof-of-concept studies in animal models have shown beneficial effects of subretinal delivery of adeno-associated vectors containing the wild-type coding sequence. [42][43][44] The young age of these patients (10, 2, and 5 years) and the knowledge of their molecular defect identified them as potentially eligible for future gene therapy trials.…”
Section: Discussionmentioning
confidence: 99%
“…For both AIPL1 and GUCY2D, proof-of-concept studies in animal models have shown beneficial effects of subretinal delivery of adeno-associated vectors containing the wild-type coding sequence. [42][43][44] The young age of these patients (10, 2, and 5 years) and the knowledge of their molecular defect identified them as potentially eligible for future gene therapy trials.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the demand for RPE65 is likely higher in humans than in dogs. 54 Another potential culprit for the transient effects is related to the stage of the retina at the time of intervention and progressive loss of trophic support (especially regarding the cones). The study by Jacobson and colleagues 52 speculated that healthier photoreceptors survived in the treated retina, whereas other, more stressed rods were already in a preapoptotic state (''at the point of no return'') and continued to die.…”
Section: Gene Delivery: Viruses Nanoparticles Physical Methodsmentioning
confidence: 99%
“…62 A high level of AIPL1 photoreceptor expression and no toxicity were documented in Aipl1 null mice and porcine eyes that received subretinal administration of AAV2/8-AIPL1. 54 As some patients with AIPL1-associated disease have a late onset and slow progression rate, it may be a good candidate for gene augmentation therapy. 63 …”
Section: Implementation Of Gene Therapy For Other Inherited Retinal Dmentioning
confidence: 99%
“…The most common LCA-causing mutation in the Caucasian population (CEP290, c.2991þ1655A.G), is responsible for 15% of all cases (den Hollander et al 2006;Perrault et al 2007;Coppieters et al 2010). In addition, the AIPL1 variant p.W278 Ã in exon 6, the GUCY2D p.R768W variant in exon 12, as well as CRB1 variants in exons 7 and 9 together explain another 20% of LCA alleles Testa et al 2011;Bujakowska et al 2012). Sequence analysis of these four exons is therefore proposed by the authors as a second prescreening step in LCA.…”
Section: Genomic Approaches For Heterogeneous Monogenic Diseasesmentioning
confidence: 99%